2005
DOI: 10.1136/bjo.2005.070508
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid treatment of periorbital haemangioma of infancy: a review of the evidence

Abstract: Aim: To systematically review the literature for corticosteroid treatment of periorbital haemangioma of infancy (HOI) and determine the relative efficacy and safety of oral, topical and intralesional corticosteroids. Methods: PubMed and the Cochrane Library were queried using keywords, and further articles were obtained by reviewing bibliographies. Inclusion and exclusion criteria were applied to create a subset of literature for analysis. Results: Systematic review revealed 81 original reports of periorbital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 37 publications
0
36
0
7
Order By: Relevance
“…This study shows that in infants with refractory massive periorbital and orbital haemangiomas, a combination of local corticosteroid treatment to the posterior subTenon's space 13 in the orbital region and directly to the lesion in the periorbital area is associated with significant improvement, both anatomically and functionally without ocular complications.…”
Section: Discussionmentioning
confidence: 98%
“…This study shows that in infants with refractory massive periorbital and orbital haemangiomas, a combination of local corticosteroid treatment to the posterior subTenon's space 13 in the orbital region and directly to the lesion in the periorbital area is associated with significant improvement, both anatomically and functionally without ocular complications.…”
Section: Discussionmentioning
confidence: 98%
“…28 The use of topical corticotherapy is also controversial in the literature and some authors have reported significant side effects and poorer efficacy when this form of treatment is used compared with intralesional corticosteroids. 12 In the present study, topical corticosteroids were used in four patients (4.1%), resulting in partial cure in three cases and complete cure in the remaining patient. Three patients had ulceration with bleeding in lesions located in the perineum and all three used the medication once a day for three weeks, often in association with a healing cream.…”
Section: Discussionmentioning
confidence: 99%
“…11 Response is generally poorer than that observed with intralesional corticosteroid therapy and side effects may occur. 12 Intralesional corticosteroid therapy is used principally in cases of periocular hemangiomas or in smaller lesions; however, its use is controversial because of possibly severe side effects. 3,13 Interferon is indicated for the treatment of alarming hemangiomas when there is a risk of death and the tumor fails to respond to treatment with oral corticoids.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Regresi spontan terjadi pada 80% hingga 85% kasus pada usia 9 tahun. Seperti telah dikemukakan di atas untuk memprediksi kemungkinan terjadinya giant hemangioma sangatlah sulit sehingga perlu dijelaskan pada orang tua untuk kontrol teratur 3-6 bulan sekali atau lebih cepat.…”
Section: Pengobatanunclassified
“…Ukurannya sangat bervariasi mulai dari beberapa millimeter hingga sentimeter. 14,15 Hemangioma dapat juga mengenai organ viseral seperti hati, limpa, usus, jatung bahkan otak yang dapat mengancam jiwa penderita. Sering tidak diketahui adanya hemangioma pada organ viseral ini sampai muncul tanda -tanda klinis yang jelas, misalnya terjadi gagal jantung pada hemangioma yang mengenai jantung, juga dapat terjadi gangguan fungsi hati jika hemangioma mengenai hati pada daerah yang cukup luas.…”
unclassified